High-thermal-conductivity water additive and preparation method thereof

By using components such as magnetic carriers, modified tea saponin and silane coupling agents, high-thermal conduction water additives are prepared, which solves the problems of poor thermal conductivity and poor stability of existing water additives, and achieves efficient heat conduction and environmentally friendly applications.

CN119505829AInactive Publication Date: 2025-02-25SHANGHAI BINGO INT TRADING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510097756.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing water additives have no significant effect in improving water thermal conductivity, poor stability, high cost and complex preparation process, and are not suitable for large-scale production and application.

Method used

The high-heat conductive water additive is prepared by using magnetic carriers, modified tea saponins and silane coupling agents. Modified tea saponin is modified by dodecyl chain to form a stable micelle structure, and the magnetic carrier improves heat conduction efficiency through the synergistic effect of nano-scale magnetic substances and carbonized ZIF-8.

Benefits of technology

It significantly improves the heat conduction efficiency of water, achieves efficient heat transfer and dispersion, reduces energy consumption, and has the characteristics of easy recycling and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505829A_ABST
    Figure CN119505829A_ABST
Patent Text Reader

Abstract

The invention relates to a high-thermal-conductivity water additive and a preparation method thereof, and belongs to the technical field of water additives. Pure natural tea saponin is adopted as a basic raw material, and a dodecyl chain is introduced under an alkaline catalysis condition to modify the tea saponin, so that tea saponin molecules can be spontaneously assembled into stable micelles in an aqueous solution, hydrogen bonds among water molecules are effectively destroyed, and the surface tension of water is remarkably reduced; the intermolecular interaction force of the modified tea saponin is enhanced, and the stability of the modified tea saponin in a high-temperature environment is enhanced. Besides, a ZIF-8 porous material is used as a carrier, a magnetic carrier easy to recover is prepared through high-temperature carbonization and confinement of magnetic substances, rich sites are provided for uniform loading of tea saponin through the high specific surface area and the regular pore channel structure of ZIF-8, and the thermal stability and the chemical stability of the material are further improved through carbonization; and through the synergistic effect of the magnetic substance and the carbonized ZIF-8, an efficient heat conduction network is constructed, and the heat conduction efficiency of the additive system is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water additives and relates to a high thermal conductivity water additive and a preparation method thereof. Background Art

[0002] Water thermal conductivity refers to the heat transfer ability of water, which mainly achieves heat transfer through vibration and collision between water molecules. However, in some application scenarios, it is necessary to further improve the thermal conductivity of water to meet specific heat transfer requirements. The efficiency of heat conduction is not only affected by the internal microstructure of the substance, but also restricted by forces such as hydrogen bonds. Therefore, it has become an important research direction to change the interaction between water molecules by adding specific substances to optimize its thermal conductivity. At present, there are some additives on the market that improve the thermal conductivity of water, but most of them have problems such as insignificant effect, poor stability, and high cost. At the same time, the preparation process of these additives is often complicated, which is not conducive to large-scale production and application. Summary of the invention

[0003] The object of the present invention is to provide a high thermal conductivity water additive and a preparation method thereof, which has the characteristics of high thermal conductivity efficiency and easy recycling.

[0004] The purpose of the present invention can be achieved through the following technical solutions: A high thermal conductivity water additive, the high thermal conductivity water additive has the following formula, in parts by weight, 60-70 parts of magnetic carrier, 20-30 parts of modified tea saponin, 3-5 parts of crosslinking agent, 180-200 parts of deionized water, The preparation method of modified tea saponin is as follows: S1-1: 3-5 parts by weight of tea saponin are added to 90-100 parts by weight of N,N-dimethylformamide, ultrasonicated for 30 min, and 8-10 parts by weight of dodecanoyl chloride and 12-16 parts by weight of sodium carbonate are added, and stirred at 50°C for 1.5 h to obtain a mixed phase A; S1-2: The mixed phase A was washed with deionized water, and then extracted with ethyl acetate solvent. The extraction equilibrium time was 50-60 s. The aqueous phase was separated with a separatory funnel. The aqueous phase and a 75% ethanol solution were mixed in a volume ratio of 1:1, and the mixture was rotary evaporated for 30 min. The mixture was then freeze-dried in a freeze dryer for 12 h to obtain the modified tea saponin.

[0005] Furthermore, the stirring speed in S1-1 is 500~600 r / min.

[0006] Furthermore, the volume ratio of the mixed phase A and ethyl acetate in the S1-2 is 1:1.

[0007] Furthermore, the freeze-drying temperature in the freeze dryer in S1-2 is -20°C.

[0008] Furthermore, the preparation method of the magnetic carrier is as follows: S5-1: 5-10 parts by weight of nano iron powder and 15-30 parts by weight of 2-methylimidazole were mixed, added to 120-140 parts by weight of methanol, ultrasonicated for 30 min, added with 120-140 parts by weight of zinc nitrate solution, and washed with methanol and deionized water at a speed of 650-750 r / min for 22-24 h, and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder B; S5-2: Powder B is placed in a muffle furnace for calcination in a nitrogen atmosphere. The calcination time is 2 to 3 hours, the calcination temperature is 400 to 500 °C, the heating rate is 5 °C / min, the cooling rate is 10 °C / min, and then placed in a ball mill for 1 hour. The powder is sieved through a 500-mesh screen to obtain the magnetic carrier.

[0009] Furthermore, the concentration of the zinc nitrate solution in S5-1 is 1 mM.

[0010] Furthermore, the ball milling speed in S5-2 is 300-400 r / min.

[0011] Furthermore, the cross-linking agent is one of the silane coupling agents KH550, KH560, and KH570.

[0012] A method for preparing a high thermal conductivity water additive, the specific steps of the preparation method are as follows: The magnetic carrier and deionized water were mixed according to the formula, stirred at a speed of 750-850 r / min for 1 h, a cross-linking agent was added, stirring was continued for 30 min, and then modified tea saponin was added, the temperature was raised from room temperature to 45-55 °C, reduced pressure was infiltrated for 1.5 h, and then rotary evaporated to obtain the high thermal conductivity water additive.

[0013] Furthermore, the pressure of the reduced pressure infiltration is set to 0.1-0.3 MPa.

[0014] The water additive prepared by the present invention can be used in a circulating water heating system at 70-90°C.

[0015] Tea saponin is a pentacyclic triterpenoid glycoside compound extracted from the Camellia oleifera plant of the Theaceae family. It is a pure natural nonionic surfactant with hydrophilic sugar bodies and hydrophobic ligand groups in its molecules. In the presence of an alkaline catalyst, a dodecyl chain is introduced into the polysaccharide part of tea saponin, which causes the molecules to spontaneously assemble into a stable micellar structure through the mutual attraction between hydrophobic groups in an aqueous solution, significantly improving the surface activity of tea saponin. The introduction of dodecyl chains also optimizes the arrangement of molecules on the surface or interface of the solution, making it more compact and orderly. This change in arrangement effectively reduces the tension of the surface or interface, and the surfactant will insert between water molecules, breaking the original arrangement structure of water molecules and destroying the hydrogen bonds between water molecules. In addition, the modified tea saponin molecules can form stronger interaction forces, thereby enhancing the stability of the molecules in the solution, which helps tea saponin maintain efficient surface activity at higher temperatures. Tea saponin itself comes from natural plants, has good biocompatibility and environmental friendliness, and will not cause harm to the environment during use.

[0016] As a porous material, ZIF-8 has a significantly high specific surface area and a regular pore structure. Its adjustable pore size and high porosity make ZIF-8 an ideal carrier for loading modified tea saponins and other active substances; high specific surface area means more active sites, which is conducive to the uniform loading and efficient utilization of tea saponins; the low density of ZIF-8 helps to reduce the weight of the entire additive system and improve the convenience in practical applications. Under high temperature conditions, the magnetic material is confined to the carbonized ZIF-8 structure, which realizes the effective introduction of magnetic functions, which not only enhances the interaction between the magnetic material and the carrier, but also significantly improves the recyclability of the material. Under the action of the magnetic field, the magnetic carrier can be easily separated from the system, which is convenient for subsequent reuse and treatment, thereby reducing environmental pollution and costs. The carbonized ZIF-8 derivative material has a more stable structure and can withstand higher temperature and pressure environments. The carbonization process also further increases the specific surface area of ​​the material, allowing more active substances such as tea saponins to be loaded on the carrier, thereby improving the performance of the entire additive. In addition, the carbonized ZIF-8 also exhibits better thermal and chemical stability, and can maintain the stability of its structure and performance under harsh working conditions. The combination of magnetic materials and ZIF-8 not only gives the additive system the ability to magnetically separate and recycle, but also achieves improved high thermal conductivity performance by optimizing the material structure and composition. The synergistic effect of nanoscale magnetic materials and carbonized ZIF-8 forms an efficient heat conduction channel, accelerating the transfer and dispersion of heat. This enables the magnetic carrier to significantly improve the thermal conductivity efficiency of the system when used as a high thermal conductivity water additive, providing strong support for industrial production and energy utilization.

[0017] As a special cross-linking agent, silane coupling agent can form strong chemical bonds between magnetic carriers and between magnetic carriers and modified tea saponin, which not only enhances the stability of the additive system, but also optimizes the heat conduction path, allowing heat to be transferred more efficiently.

[0018] The high thermal conductivity water additive of the present invention not only has excellent thermal conductivity performance, but also has the advantage of being non-corrosive, ensuring that the water additive will not cause corrosion to the environment or equipment during long-term use, thereby constructing an efficient and safe thermal conduction system.

[0019] Beneficial effects of the present invention: (1) Tea saponin is modified with dodecyl chains so that it spontaneously assembles into stable micelles in aqueous solution, effectively enhancing its ability to reduce surface tension. The introduction of dodecyl chains optimizes the arrangement of tea saponin molecules on the surface or interface of the solution, making them more compact and orderly, further reducing the surface or interface tension and destroying the hydrogen bonds between water molecules. The interaction force between the modified tea saponin molecules is significantly enhanced, which improves its stability in solution and ensures that it maintains high surface activity at higher temperatures. Tea saponin is derived from natural plants and has good biocompatibility and environmental friendliness. It will not cause harm to the environment during use.

[0020] (2) The synergistic effect of nano-magnetic materials and carbonized ZIF-8 as carrier materials forms an efficient heat conduction channel, which accelerates the transfer and dispersion of heat. When the magnetic carrier is used as a high thermal conductivity water additive, it can significantly improve the thermal conduction efficiency of the system and effectively save energy. In addition, it also gives the additive system the ability of magnetic separation and recovery, providing strong support for industrial production and energy utilization. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.

[0022] Figure 1 This is the actual energy saving situation of the water circulation heating system after adding Example 1, where the x-axis is the time axis and the y-axis is the change in energy consumption performance. DETAILED DESCRIPTION

[0023] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.

[0024] In the embodiments of the present invention and the comparative examples: Tea saponin: purchased from Panier (Shaanxi) Industrial Co., Ltd.; N,N-dimethylformamide: purchased from Shanghai Denuo Chemical Co., Ltd.; Dodecanoyl chloride: purchased from Shanghai Bangcheng Chemical Co., Ltd. Sodium carbonate: purchased from Nanjing Chemical Reagent Co., Ltd. Ethyl acetate: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Ethanol: purchased from Changshu Hongsheng Fine Chemical Co., Ltd.; Nano iron powder: purchased from Shanghai Yien Chemical Technology Co., Ltd. 2-Methylimidazole: purchased from Jiangsu Zhenri Chemical Co., Ltd.; Methanol: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Zinc nitrate hexahydrate: purchased from Shanxi Bocheng New Materials Technology Co., Ltd.; Silane coupling agents KH550, KH560, and KH570 were purchased from Sichuan Cullinan Technology Co., Ltd.

[0025] Example 1 A high thermal conductivity water additive, the high thermal conductivity water additive formula 1 is as follows, in parts by weight, 65 parts of magnetic carrier, 25 parts of modified tea saponin, 4 parts of silane coupling agent KH550, 190 parts of deionized water, The preparation method of modified tea saponin is as follows: S1-1: 4 parts by weight of tea saponin were added to 95 parts by weight of N,N-dimethylformamide, ultrasonicated for 30 min, and 9 parts by weight of dodecanoyl chloride and 14 parts by weight of sodium carbonate were added, and stirred at 50°C and 550 r / min for 1.5 h to obtain a mixed phase A; S1-2: The mixed phase A was washed with deionized water, and then extracted with ethyl acetate solvent, wherein the volume ratio of the mixed phase A to ethyl acetate was 1:1, and the extraction equilibrium time was 55 s. The aqueous phase was separated using a separatory funnel, and the aqueous phase and a 75% ethanol solution were mixed in a volume ratio of 1:1, rotary evaporated for 30 min, and then placed in a freeze dryer at -20 ° C for lyophilization for 12 h to obtain the modified tea saponin.

[0026] The preparation method of the magnetic carrier is as follows: S5-1: 7 parts by weight of nano iron powder and 25 parts by weight of 2-methylimidazole were mixed, added to 130 parts by weight of methanol, ultrasonicated for 30 min, added with 130 parts by weight of 1 mM zinc nitrate solution, rotated at 700 r / min for 23 h, washed with methanol and deionized water, and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder B; S5-2: Powder B was placed in a muffle furnace for calcination in a nitrogen atmosphere for 2.5 h at a calcination temperature of 450 °C, a heating rate of 5 °C / min, and a cooling rate of 10 °C / min. Powder B was then placed in a ball mill for 1 h at a ball milling speed of 350 r / min and passed through a 500-mesh sieve to obtain the magnetic carrier.

[0027] A method for preparing a high thermal conductivity water additive, the specific steps of the preparation method are as follows: According to formula 1, the magnetic carrier and deionized water were mixed, stirred at a speed of 800 r / min for 1 h, silane coupling agent KH550 was added, stirring was continued for 30 min, and then modified tea saponin was added, the temperature was raised from room temperature to 50 ° C, and the reduced pressure infiltration was performed for 1.5 h, the pressure of the reduced pressure infiltration was set to 0.2 MPa, and then rotary evaporation was performed to obtain the high thermal conductivity water additive.

[0028] Example 2 A high thermal conductivity water additive, the high thermal conductivity water additive formula 2 is as follows, in parts by weight, 60 parts of magnetic carrier, 20 parts of modified tea saponin, 3 parts of silane coupling agent KH560, 180 parts of deionized water, The preparation method of modified tea saponin is as follows: S1-1: 3 parts by weight of tea saponin were added to 90 parts by weight of N,N-dimethylformamide, ultrasonicated for 30 min, and 8 parts by weight of dodecanoyl chloride and 12 parts by weight of sodium carbonate were added, and stirred at 50°C and 500 r / min for 1.5 h to obtain a mixed phase A; S1-2: The mixed phase A was washed with deionized water, and then extracted with ethyl acetate solvent, wherein the volume ratio of the mixed phase A to ethyl acetate was 1:1, and the extraction equilibrium time was 50 s. The aqueous phase was separated using a separatory funnel, and the aqueous phase and a 75% ethanol solution were mixed in a volume ratio of 1:1, rotary evaporated for 30 min, and then placed in a freeze dryer at -20 ° C for lyophilization for 12 h to obtain the modified tea saponin.

[0029] The preparation method of the magnetic carrier is as follows: S5-1: 5 parts by weight of nano iron powder and 15 parts by weight of 2-methylimidazole were mixed, added to 120 parts by weight of methanol, ultrasonicated for 30 min, added with 120 parts by weight of 1 mM zinc nitrate solution, rotated at 650 r / min for 22 h, washed with methanol and deionized water, and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder B; S5-2: Powder B is placed in a muffle furnace for calcination in a nitrogen atmosphere. The calcination time is 2 h, the calcination temperature is 400 °C, the heating rate is 5 °C / min, the cooling rate is 10 °C / min, and then placed in a ball mill for 1 h at a ball mill speed of 300 r / min. The powder is sieved through a 500-mesh screen to obtain the magnetic carrier.

[0030] A method for preparing a high thermal conductivity water additive, the specific steps of the preparation method are as follows: According to formula 2, the magnetic carrier and deionized water were mixed, stirred at a speed of 750 r / min for 1 h, silane coupling agent KH560 was added, stirring was continued for 30 min, and then modified tea saponin was added, the temperature was raised from room temperature to 45 °C, and the reduced pressure infiltration was performed for 1.5 h. The pressure of the reduced pressure infiltration was set to 0.1 MPa, and then rotary evaporation was performed to obtain the high thermal conductivity water additive.

[0031] Example 3 A high thermal conductivity water additive, the high thermal conductivity water additive formula 3 is as follows, in parts by weight, 70 parts of magnetic carrier, 30 parts of modified tea saponin, 5 parts of silane coupling agent KH570, 200 parts of deionized water, The preparation method of modified tea saponin is as follows: S1-1: 5 parts by weight of tea saponin were added to 100 parts by weight of N, N-dimethylformamide, ultrasonicated for 30 min, and 10 parts by weight of dodecanoyl chloride and 16 parts by weight of sodium carbonate were added, and stirred at 50°C and 600 r / min for 1.5 h to obtain a mixed phase A; S1-2: The mixed phase A was washed with deionized water, and then extracted with ethyl acetate solvent, wherein the volume ratio of the mixed phase A to ethyl acetate was 1:1, and the extraction equilibrium time was 60 s. The aqueous phase was separated using a separatory funnel, and the aqueous phase and a 75% ethanol solution were mixed in a volume ratio of 1:1, rotary evaporated for 30 min, and then placed in a freeze dryer at -20 ° C for lyophilization for 12 h to obtain the modified tea saponin.

[0032] The preparation method of the magnetic carrier is as follows: S5-1: 10 parts by weight of nano iron powder and 30 parts by weight of 2-methylimidazole were mixed, added to 140 parts by weight of methanol, ultrasonicated for 30 min, added with 140 parts by weight of 1 mM zinc nitrate solution, rotated at 750 r / min for 24 h, washed with methanol and deionized water, and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder B; S5-2: Powder B is placed in a muffle furnace for calcination in a nitrogen atmosphere. The calcination time is 3 h, the calcination temperature is 500 °C, the heating rate is 5 °C / min, the cooling rate is 10 °C / min, and then placed in a ball mill for 1 h at a ball mill speed of 400 r / min. The powder is sieved through a 500-mesh screen to obtain the magnetic carrier.

[0033] A method for preparing a high thermal conductivity water additive, the specific steps of the preparation method are as follows: According to formula 3, the magnetic carrier and deionized water were mixed, stirred at a speed of 850 r / min for 1 h, silane coupling agent KH570 was added, stirring was continued for 30 min, and then modified tea saponin was added, the temperature was raised from room temperature to 55 °C, and the reduced pressure infiltration was performed for 1.5 h. The pressure of the reduced pressure infiltration was set to 0.3 MPa, and then rotary evaporation was performed to obtain the high thermal conductivity water additive.

[0034] Comparative Example 1 The tea saponin was not modified, and the remaining steps were consistent with those in Example 1.

[0035] Comparative Example 2 No muffle furnace calcination treatment was performed in the preparation of the magnetic carrier, and the remaining steps were consistent with Example 1.

[0036] Comparative Example 3 No nano iron powder is added in the preparation of the magnetic carrier, and the remaining steps are consistent with Example 1.

[0037] Performance Testing: The actual energy saving of the embodiment and the comparative example was tested. Deionized water was used as the heat energy carrier of the whole system, and 1‰ water additive was added to the deionized water to improve the thermal efficiency and reduce the heating power consumption. The circulating water system without water additive was used as a comparison, and the time and power consumption were recorded to calculate the actual energy saving.

[0038] The experimental data are recorded in the following table:

[0039] According to the data of the embodiments and comparative examples, tea saponin is modified by dodecanoyl chloride, and carbonized ZIF-8 with confined magnetic material is prepared as a carrier, and a silane coupling agent is used to enhance the compatibility between the modified tea saponin and the carrier, and the modified tea saponin is loaded on the surface and inside of the magnetic carrier to prepare a water additive, which only needs to be added in a small amount to the circulating water heating system to effectively reduce energy consumption.

[0040] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A high thermal conductivity water additive, characterized in that: The high thermal conductivity water additive is formulated as follows: by weight, 60-70 parts of magnetic carrier, 20-30 parts of modified tea saponin, 3-5 parts of cross-linking agent, and 180-200 parts of deionized water. The preparation method of modified tea saponin is as follows: S1-1: 3-5 parts by weight of tea saponin are added to 90-100 parts by weight of N,N-dimethylformamide, ultrasonicated for 30 min, and 8-10 parts by weight of dodecanoyl chloride and 12-16 parts by weight of sodium carbonate are added, and stirred at 50°C for 1.5 h to obtain a mixed phase A; S1-2: The mixed phase A was washed with deionized water, and then extracted with ethyl acetate solvent. The extraction equilibrium time was 50-60 seconds. The aqueous phase was separated with a separatory funnel. The aqueous phase and a 75% ethanol solution were mixed in a volume ratio of 1:1, and the mixture was rotary evaporated for 30 minutes. The mixture was then freeze-dried in a freeze dryer for 12 hours to obtain the modified tea saponin.

2. A high thermal conductivity water additive according to claim 1, characterized in that: The stirring speed in S1-1 is 500-600 r / min.

3. A high thermal conductivity water additive according to claim 1, characterized in that: The volume ratio of the mixed phase A and ethyl acetate in the S1-2 is 1:

1.

4. A high thermal conductivity water additive according to claim 1, characterized in that: The freeze-drying temperature in the freeze dryer in S1-2 is -20°C.

5. The high thermal conductivity water additive according to claim 1, characterized in that: The preparation method of the magnetic carrier is as follows: S5-1: 5-10 parts by weight of nano iron powder and 15-30 parts by weight of 2-methylimidazole were mixed, added to 120-140 parts by weight of methanol, ultrasonicated for 30 min, added with 120-140 parts by weight of zinc nitrate solution, and washed with methanol and deionized water at a speed of 650-750 r / min for 22-24 h, and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder B; S5-2: Powder B is placed in a muffle furnace for calcination in a nitrogen atmosphere. The calcination time is 2 to 3 hours, the calcination temperature is 400 to 500 °C, the heating rate is 5 °C / min, the cooling rate is 10 °C / min, and then placed in a ball mill for 1 hour. The powder is sieved through a 500-mesh screen to obtain the magnetic carrier.

6. A high thermal conductivity water additive according to claim 5, characterized in that: The concentration of the zinc nitrate solution in S5-1 is 1 mM.

7. A high thermal conductivity water additive according to claim 5, characterized in that: The ball milling speed in S5-2 is 300-400 r / min.

8. The high thermal conductivity water additive according to claim 1, characterized in that: The cross-linking agent is one of the silane coupling agents KH550, KH560 and KH570.

9. A method for preparing the high thermal conductivity water additive according to claims 1 to 8, characterized in that: The specific steps of the preparation method are as follows: The magnetic carrier and deionized water were mixed according to the formula, stirred at a speed of 750-850 r / min for 1 h, a cross-linking agent was added, stirring was continued for 30 min, and then modified tea saponin was added, the temperature was raised from room temperature to 45-55 °C, reduced pressure was infiltrated for 1.5 h, and then rotary evaporated to obtain the high thermal conductivity water additive.

10. The method for preparing a high thermal conductivity water additive according to claim 9, characterized in that: The pressure of the reduced pressure infiltration is set to 0.1-0.3 MPa.

Citation Information

Patent Citations

  • Preparation method of tea saponin laurate surfactant and product thereof

    CN103804462A

  • Preparing method of ferulic acid microemulsion preparation

    CN105687134A

  • Silicon dioxide@silver shell-core structural nanometer fluid and preparation method thereof

    CN106928909A

  • Nanofluid heat-transfer working medium for solar collector tube and preparation method of nanofluid heat-transfer working medium

    CN107974240A

  • Magnetic field regulation and control solar heat collection device

    CN113587454A